Kontribusi Perilaku Guru dan Metode Pembelajaran dalam Meningkatkan Prestasi Belajar Al-Qur'an Hadits - Budi Santoso; Maragustam Siregar (Fahima, 2022)
This study aims to: (1) determine the effect of teacher behaviour on the learning achievement of Al Qur'an Hadith students of class XI MAN 3 Boyolali in the 2020/2021 school year. (2) find out the effect of learning methods on the learning achievement of Al Qur'an Hadith students of class XI MAN 3 Boyolali in the 2020/2021 school year. (3) determine the effect of teacher behaviour and learning methods on the learning achievement of Al Qur'an Hadith students of class XI MAN 3 Boyolali in the 2020/2021 school year. This study uses a quantitative approach. The population is 93 students, and data is taken through questionnaires, interviews, observations and documentation of the value of the Al-Qur'an Hadith even semester 2020/2021. The research was analyzed using the product-moment formula. Research results (1). The influence of teacher behaviour on learning achievement of Al Qur'an Hadith after being completed with the product-moment formula, the value of rxy = 0.450, consulted with rtable at a significant level of 5% N = 93 rtable = 0.207 and considerable level 1% N = 93 rtable = 0.270. The hypothesis is that teacher behaviour positively influences the learning achievement of Al-Qur'an Hadith students in class XI MAN 3 Boyolali in the 2020/2021 academic year, which is accepted or tested. (2). The effect of learning methods on learning achievement of Al Qur'an Hadith students of class XI MAN 3 Boyolali in the 2020/2021 school year after being completed with the product-moment formula, the final value of rXY = 0.265, when consulted with rtable with a significant level of 5% N = 93 rtable = 0.202 and if consulted with rtable 1% significance level N = 93 rtable = 0.263. The hypothesis is that learning methods positively influence the learning achievement of Al-Qur'an Hadith students in class XI MAN 3 Boyolali in the 2020/2021 academic year, whether it is accepted or tested. (3). The influence of teacher behaviour and learning methods on learning achievement of Al-Qur'an Hadith students of class XI MAN 3 Boyolali in the 2020/2021 school year after completing the product-moment formula, the final value rXY = 0.414, consulted with rtable at a significant level of 5% N = 93 rtable = 0.202. When consulted with rtable at a significant level of 1%, N = 93 rtable = 0.263. Based on the hypothesis that there is a positive influence on teacher behaviour and learning methods on the learning achievement of Al Qur'an Hadith students of class XI MAN 3 Boyolali for the 2020/2021 school year are accepted or tested because the value of rxy > rtable, either 5% or 1%.